Capsosiphon fulvescens Glycoproteins Enhance Probiotics-Induced Cognitive Improvement in Aged Rats - Oh, Jeong Hwan (Nutrients, 2020)
Aging-induced cognitive dysfunction can be regulated by probiotics through bidirectional communication with the brain. This study aimed to investigate whether Capsosiphon fulvescens glycoproteins (Cf-hGP) enhanced probiotic-induced improvement of memory in aged rats and the underlying mechanism in the dorsal hippocampus. Cf-hGP were isolated using lectin resin. Cf-hGP (15 mg/kg/day) and/or Lactobacillus plantarum (L. plantarum) (10(9) CFU/rat/day) were orally administered once a day for 4 weeks. Co-treatment with Cf-hGP and L. plantarum synergistically improved spatial memory in aged rats, which was overturned by functional blocks of brain-derived neurotrophic factor (BDNF) signaling. Increases in BDNF expression and nuclear factor erythroid 2-related factor 2 (Nrf2) phosphorylation were accompanied by mono- and/or co-administration in the dorsal hippocampus, while c-Jun N-terminal kinase (JNK) phosphorylation and glucose-regulated protein 78 expression were decreased. These synergistic effects were downregulated by blocks of BDNF/Nrf2-mediated signaling. In particular, co-treatment, not mono-treatment, reduced phosphorylation of eukaryotic elongation factor 2 (eEF2) regulated by eEF2 kinase and protein phosphatase 2A. Additionally, co-treatment downregulated the interaction between eEF2 kinase and JNK. These data demonstrated that cognitive impairment in aged rats was synergistically diminished by co-treatment with Cf-hGP and L. plantarum through BDNF-mediated regulation of Nrf2 and eEF2 signaling pathways in the dorsal hippocampus.